TIMBRE ALLUSION AS A CONDITIONAL STYLIZATION ОF SONORITY - Stronko, Boryslav (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The Relevance of the study is conditioned by the specific ploblem of timbre allusion as a result of the interaction between actual sound and the sound associations of performer and the listener, intentionally evoked by the composer. Тhe main objective of the study is to highlight the distinctions between this phenomenon and related concepts such as timbre coloring and illusory timbre, thereby refining the relevant musicological terminology. The methodology is based on methods of textual analysis in music and, especially, comparison. How the study was done: was analyzed a series of illustrative examples from piano and symphonic literature, with engaging of significant analogies between playing styles of different types. The main results and conclusions. The use of timbre allusions is noted starting from 18thcentury music, with their purpose not being the literal reproduction of other timbres, but rather a symbolic reference to them. The study reveals such means of actualizing timbre allusions as articulation, rhythm, register, intervallic structure and playing manner typical to other instruments. In general, it refers to a style of music-making reconstituted by sound means of the original instrument as a basis for association with an absent timbre. Consequently, this style is defined as a timbreintonational thesaurus shared among the composer, performer and listener — an intersubjective factor essential for a holistic perception of a music composition. Special attention is paid to the role of time in timbre allusion — as an appeal to a common past of composer, performer and audience, as well as to the isomorphism of temporally distinct events. Тhe timbre allusion engages not only actual sound in the realm of artistic influence but also the individual and collective experience of perceiving musical works across stylistic, genre, and technical diversity —i.e. memory space. The significance of the study onsists of further and deeper conveying of interactive side of musical timbre perception. As a perspective, two main directions are outlined for further research on the topic: external and internal. The first of them relates to the real-acoustic enriching of a musical instrument’s sound influenced by the timbres of other instruments. The second of them focuses on the dual-level perception of the timbre-intonational domain of music and the interactive relationship between the musical work and the listener.